Pengaruh Gaya Mengajar Guru terhadap Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam di SMP Muhammadiyah 1 Wonosobo - Qosdan Dawami; Mohammad Sakir; Ali Mu’tafi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The objective of this study is to determine the influence of teacher teaching style on student learning motivation in Islamic Religious Education at SMP Muhammadiyah 1 Wonosobo. The approach used in this study is a quantitative approach with a causal associative method. Data collection was conducted through the distribution of questionnaires to 144 respondents selected using probability sampling technique. Data were collected using questionnaires for the learning motivation variable and the teaching style variable. The technique analysis applied in this study is a simple linear regression analysis with the help of SPSS program. The results of this study indicated the the teacher teaching style has a significant and positive influence on student learning motivation in Islamic Religious Education subjects at SMP Muhammadiyah 1 Wonosobo. This result was proven by the results of the T-test which showed that the significance value of the regression model of this study is greater than the significance level value. Based on these results, it is suggested for Islamic Religious Education teachers at SMP Muhammadiyah 1 Wonosobo to apply adaptive and innovatice teaching style to maintain and increase student learning motivation.